Norms and the Evolution of Leaders' Followership - Antonio Cabrales; Esther Hauk (Center for Economic Studies and ifo Institute (CESifo), 2022)
In this paper we model the interaction between leaders, their followers and crowd followers in a coordination game with local interaction. The steady states of a dynamic best-response process can feature a coexistence of Pareto dominant and risk dominant actions in the population. The existence of leaders and their followers, plus the local interaction, which leads to clustering, is crucial for the survival of the Pareto dominant actions. The evolution of leader and crowd followership shows that leader followership can also be locally stable around Pareto dominant leaders. The paper answers the questions (i) which Leader should be removed and (ii) how to optimally place leaders in the network to enhance payoff dominant play.
Keywords: C70; D85; 330; coordination games; leaders; followers; evolution